CLINICAL CHARACTERISTICS, ETIOLOGICAL PATTERNS, AND PREDICTORS OF DISCHARGE OUTCOMES IN CEREBRAL VENOUS THROMBOSIS: A COHORT STUDY AT A TERTIARY NEUROLOGY CENTER (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics, analyze the etiological spectrum, and identify independent prognostic factors for discharge outcomes in patients with cerebral venous thrombosis.Research methods: A retrospective cohort study was conducted on 176 adult patients diagnosed with cerebral venous thrombosis at Cho Ray Hospital from September 2023 to September 2025. Thrombotic burden was quantified using the VSSS, and discharge outcomes were assessed using the modified Rankin Scale (mRS). Multivariable logistic regression was performed to determine predictors of poor outcome (mRS > 2).Results: The mean age was 44.6 ± 14.6 years, with females accounting for 75% of cases; 88.1% had subacute onset. After comprehensive evaluation, the proportion of truly idiopathic cases decreased to only 23.3%. Deficiency of natural anticoagulants (protein C, protein S, and antithrombin III) accounted for 58% of patients; oral contraceptive use was identified in 39.4% of women; and risk factor clustering (≥ 2 factors) was present in 36.4%. Despite parenchymal hemorrhage in 50% at admission, early anticoagulation therapy (Heparin, 88.1%) still resulted in 69.9% achieving mRS 0-2, while in-hospital mortality was only 1.7%. Impaired consciousness at admission was the strongest predictor of poor outcome (OR = 8.33; 95% CI: 3.43-20.26; p < 0.001), along with parenchymal hemorrhage (OR = 3.79), limb weakness (OR = 2.47), age (OR = 1.06), and leukocytosis (OR = 1.14).Conclusion: Cerebral venous thrombosis in Vietnam is shifting toward modern risk factors and predominantly follows the two-hit hypothesis. Early anticoagulation is safe even in the presence of hemorrhage. Impaired consciousness is a critical red flag for deep venous system involvement, necessitating intensive neurocritical care
Keywords: Cerebral venous thrombosis, prognosis, risk factors.